2019
DOI: 10.3389/feart.2019.00210
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Multi-Scale Spatio-Temporal Modeling of Precipitation in the Indus Watershed

Abstract: The Indus watershed is a highly populated region that contains parts of India, Pakistan, China, and Afghanistan. Changes in precipitation patterns and rates of glacial melt have significantly impacted the region in recent years, and climate change is projected to result in further serious human and environmental consequences. To understand the climate dynamics of the Indus watershed and surrounding regions, reanalysis and satellite data from products such as APHRODITE-2, TRMM, ERA5, and MERRA-2 are often used,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Until such improved near real-time precipitation products are made available, precipitation climatologies, such as the GPCC Climatology, could at least be used to correct the mean bias in precipitation for areas such as the Indus basin. Another recent study of precipitation products [13] also showed that MERRA-2 tended to have lower precipitation around the Indus watershed than APHRODITE and TMPA, while ERA-5 had higher precipitation, although that study did not evaluate how these products compared to station observations. GPCC, supported by CRU, showed a significant increase in precipitation over the Indus basin since the end of the 19th Century.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Until such improved near real-time precipitation products are made available, precipitation climatologies, such as the GPCC Climatology, could at least be used to correct the mean bias in precipitation for areas such as the Indus basin. Another recent study of precipitation products [13] also showed that MERRA-2 tended to have lower precipitation around the Indus watershed than APHRODITE and TMPA, while ERA-5 had higher precipitation, although that study did not evaluate how these products compared to station observations. GPCC, supported by CRU, showed a significant increase in precipitation over the Indus basin since the end of the 19th Century.…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, there is high uncertainty owing to divergent behavior of climate models and limited ground observations [9][10][11]. Sparsity and discontinuity of climate and hydrologic observations make it difficult to evaluate the accuracy of hydrologic and climate models and create gaps in the scientific understanding needed to provide evidence for policy decisions [12,13]. Globally, there is recognition of an increased need for employing statistical analyses to provide better information about long-term changes and variability of precipitation as a result of the changing climate and consequent greater exposure to risks such as droughts and floods [14].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the climatologies for precipitation amount, number of days with precipitation over a given threshold and cloudiness of the different experiments were intercompared for the BASE, ARI and ARCI simulations. The ERA5 (Hrarsbach and Dee, 2016) reanalysis data were used to calculate the added value of the aerosol experiments, since they have already been validated for precipitation (Albergel et al, 2018;Christensen et al, 2019;Hwang et al, 2019). Also represented are the comparison of the annual and seasonal climatologies for other atmospheric fields such as sea level pressure (slp), geopotential height (Z) and temperature (T ) at 1000, 750 and 500 mb, maximum and minimum temperatures (tasmax, tasmin), daily temperature range (dtr), and solar radiation at surface (rsds) as well as mean temporal fields of the particulate matter (PM 10 , PM 2.5 ), BC (black carbon) and AOD.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, the climatologies for precipitation amount, number of days with precipitation over a given threshold and cloudiness of the different experiments have been intercompared for BASE, ARI and ACI simulations. The data used to evaluate the added value of the aerosol experiments was the ERA5 (Hrarsbach and Dee, 2016) reanalysis, since it has already been validated for precipitation (Albergel et al, 2018;Christensen et al, 2019;Hwang et al, 2019).…”
Section: Methodsmentioning
confidence: 99%